Early stages wind load assessment using Computational Fluid Dynamics: The new Bologna Stadium roof. (January 2023) - Xing, Jin; Patruno, Luca; de Miranda, Stefano; Pinardi, Stefano; Majowiecki, Massimo; Ubertini, Francesco
Abstract: The use of Computational Fluid Dynamics (CFD) is rapidly expanding, allowing to complement traditional wind tunnel tests even in the case of extremely complex geometries at reasonable computational costs. In this contribution, we report the experience gained in the preliminary study of the new roof over the Bologna Stadium. The study, performed prior to wind tunnel tests, is meant to provide the designer a first evaluation of wind loads in early design stages, with classical wind tunnel tests planned at the final design stage. The most critical loading conditions are identified and the structural response evaluated. Finally, the structural response sensitivity to damping, which is difficult to be accurately evaluated a priori, is assessed. The study shows how early CFD simulations can effectively complement traditional wind tunnel tests in the project development.